Green immobilization of CdS-Pt nanoparticles on recombinant Escherichia coli boosted by overexpressing cysteine desulfurase for photocatalysis application. (December 2021) - Liu, Ya; Pei, Rui; Huang, Zhongliang; Xiao, Jingran; Yao, Ayan; Xu, Kaiji; Li, Yixin; Ullah, Shafqat; Yu, Zongzhong; Wang, Yuanpeng; Zhou, Shu-Feng; Zhan, Guowu
Abstract: Herein, we propose a facile synthetic strategy for biogenic photocatalyst by sequentially immobilizing CdS and Pt nanoparticles (NPs) on engineered recombinant Escherichia coli ( e-E. coli ) strains. In particular, we transferred the cysteine desulfurase gene to the heterologous host to overexpress cysteine desulfurase and the resulting e-E. coli strain could serve as a biofactory for the extracellular growth of CdS NPs involving catalyzing L-cysteine (Cys) to form a reactive sulfur source, followed by the precipitation of CdS via the reaction between Cd 2+ ions and the locally concentrated active sulfur source around the strain. The subsequent modification of e-E. coli /CdS composites with noble metal Pt NPs further enhanced the catalytic degradation performance towards organic dyes, due to suppressing the recombination of the photogenerated electron-hole pairs. Accordingly, the ternary e-E. coli /CdS/Pt composites emerged as robust photocatalysts for pollutant degradation in waste-water treatment, which is promising for environmental remediation in ambient conditions. Graphical abstract: Unlabelled Image Highlights: Recombinant Escherichia coli was designed to overexpress cysteine desulfurase. e-E. coli transforms Cys to active sulfur sources to form e-E. coli /CdS composite. The formation of e-E. coli /CdS composite is highly dependent on incubation time. Pt effectively suppresses the recombination of photogenerated electron-hole pairs. Ternary e-E. coli /CdS/Pt exhibited excellent photocatalytic degradation activity.